Fiqih dan Pendidikan Karakter di Era Modern: Tinjauan Literatur - Endy Dharma Pangestu; Chanifudin (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the role of fiqh in character education for students in the modern era through a systematic literature review approach. The background of this research is based on the increasing moral challenges faced by the younger generation due to technological advancement, globalization of values, and rapid social change, which require strengthening character education based on Islamic values. The research method employed is a systematic literature review of journal articles, academic books, and empirical studies published over the past ten years from reputable scientific sources. The findings indicate that fiqh has a significant contribution to the development of students’ character, particularly in aspects such as religiosity, discipline, responsibility, honesty, tolerance, and social awareness. Fiqh learning that is implemented through contextual approaches, value habituation, practical activities, and teacher role modeling has proven effective in bridging theoretical understanding of Islamic law with its application in daily life. Furthermore, fiqh is adaptive and relevant to be developed within the context of character education in the digital era without neglecting the principles of Islamic law. This study concludes that the integration of fiqh and character education serves as an essential foundation for developing holistic, contextual, and responsive Islamic education in facing modern challenges